Advancing co-creation in local governance the role of coping strategies and constructive hybridization - Røiseland, Asbjørn 1963-; Sørensen, Eva 1957-; Torfing, Jacob 1963- (Edward Elgar, 2024)
This innovative book presents a theoretical framework for understanding co-creation and the ways that public leaders may cope with the conflicts, dilemmas and paradoxes that arise when co-creation clashes with existing governance paradigms, such as old-style bureaucracy and New Public Management.
Keywords: Aufsatzsammlung